Effects of Social Media Marketing Activities on Perceived Values, Online Brand Engagement, and Brand Loyalty - Nguyen, Ngoc Minh; Nguyen, Huyen Thi; Cao, Thao Anh (Emerging Science Journal, 2024)
This study aims to validate the model on the effects of social media marketing activities on the perceived values of social media marketing activities and the effects of these perceived values on online brand engagement and, consequently, on brand loyalty. The data used in this study were collected through an online self-administered survey of 501 young social media users in Vietnam. Partial Least Squares Algorithm, Bootstrapping, PLSpredict/CVPAT, and Multi-Group Analysis methods embedded in Smart-PLS software were used to validate the measurement model and test the research hypotheses. The findings confirm that the positive effects of social media marketing activities on brand loyalty are transmitted through the perceived values of these activities and online brand engagement. These effects are more substantial for luxury brands compared to non-luxury brands. Importantly, our study offers a new approach to explaining the impact of social media marketing activities on brand loyalty by focusing on the perceived values of these activities and their effects on online brand engagement. To enhance brand loyalty, businesses should prioritize creating hedonic and utilitarian values through their social media marketing activities and use these values and online brand engagement as key performance indicators for planning and controlling their strategies. Doi: 10.28991/ESJ-2024-08-05-017 Full Text: PDF